Development of optimal water distribution system design and operation approach considering hydraulic and water quality criteria in many-objective optimization framework. Issue 2 (21st March 2022) - Choi, Young Hwan
Abstract: Water distribution systems (WDSs) are major infrastructure, and it needs to consider economic, hydraulic stability, and water quality safety to optimal design and operation of WDSs. However, the previous studies related to WDS design and operation were focused on each field (i.e. design: optimal pipe diameter, pump sizing, and valve location; operation: optimal pump scheduling, etc.) even though the WDS design and operation have a correlation. Therefore, to achieve economic feasibility, hydraulic stability, and water quality safety under WDS design and operation process, this study develops an optimal WDS design and operation approach considering hydraulic and water quality criteria in the many-objective optimization framework. To consider design and operation, this study applies three objective functions to minimize the total design and operation cost (i.e. the pipe cost, pump construction, and pump operation cost), maximize system robustness, and minimize the amount of chlorine requisition simultaneously under the hydraulic and quality constraints. The proposed optimal WDS design and operation model was applied to the two-stage optimization procedures. The first process determined the optimal pipe diameter set. The second process determined the optimal pump construction and scheduling considering three objective functions such as the total pump cost, the system robustness, and the quantity of the required residual chlorine for determining optimally the available number of pumps, capacity, and scheduling. For the optimization, the self-adaptive multi-objective harmony search is used and a famous benchmark network for the optimal design and pump operation of WDSs is applied to verify the proposed approach. This study can provide a new perspective on WDS design and operation technique considering the essential design factors to the water utility. Graphical Abstract: